THE DOCTRINE OF CAUSALITY IN CRIMINAL LAW IN THE FIELD OF TAXATION IN INDONESIA - Hartanto, Anton (Journal of Tax Law and Policy, 2023)
The complexity of tax evasion and the unregulated causality doctrine in the law (KUHP) and tax law show the need and urgency to answer the problem of the ideal criminal concept in the field of taxation in the future. The analysis and discussion concluded that the ideal concept in handling complex criminal offenses in the field of taxation could be done by regulating the teaching of causality and its modification. The adoption of the doctrine of causality and its modification in the criminal provisions in the field of taxation can provide a guarantee of criminal liability in the field of taxation to any person who has actually caused a certain result prohibited in tax crimes. One of them is by considering the existence of novus actus interveniens.